The Design and Screening of Drugs to Prevent Acquired Sensorineural Hearing Loss - Mukherjea, Debashree (2011)
INTRODUCTION: Sensorineural hearing loss affects a high percentage of the population. Ototoxicity is a serious and pervasive problem in patients treated with cisplatin. Strategies to ameliorate ototoxicity without compromising on antitumor activity of treatments are urgently needed. Similar problems occur with aminoglycoside antibiotic therapy for infections. Noise-induced hearing loss affects a large number of people. The use of ear protection is not always possible or effective. The prevention of hearing loss with drug therapy would have a huge impact in reducing the number of persons with hearing loss from these major causes. AREAS COVERED: This review discusses significant research findings dealing with the use of protective agents against hearing loss caused by cisplatin, aminoglycoside antibiotics and noise trauma. The efficacy in animal studies and the application of these protective agents in clinical trials that are ongoing are presented. EXPERT OPINION: The reader will gain new insights into current and projected future strategies to prevent sensorineural hearing loss from cisplatin chemotherapy, aminoglycoside antibiotic therapy and noise exposure. The future appears to offer numerous agents to prevent hearing loss caused by cisplatin, aminoglycoside antibiotics and noise. Novel delivery systems will provide ways to guide these protective agents to the desired target areas in the inner ear and will circumvent problems with therapeutic interference of anti-tumor and antibiotics agents and will minimize undesired side effects.